(untitled) (Annals of Medical Research, 2023)
Aim: The Internet is a widespread and increasingly used resource for obtaining medical information by both patients and public health care providers. Our aim in this study was to evaluate the accuracy and quality of the information in idiopathic ventricular arrhythmia (IVA) videos posted on YouTube. Materials and Methods: "Idiopathic Ventricular Dysrhythmia" or "Idiopathic Ventricular Arrhythmia" keywords of YouTube search engine were queried. 48 videos suitable for 2-15 minutes were included in the study. The popularity of videos was judged by an index called the video strength index (VPI). The reliability of the videos was assessed with the DISCERN score. The quality of the information resource measured using the Global Quality Score (GQS). Results: The average duration of the videos was 444±220 seconds, and the average number of views is 11241±865, with a median view count of 1085 (151-22012). The median VPI value of the videos was 4 (0-34), the mean DISCERN score was 3.1±0.5, and the mean GQS score was 3.6±1.1. Conclusion: YouTube serves as an easily accessible and inexpensive data center for patient education and understanding the illness. However, the popular YouTube videos on IVA administration appear to be largely lacking in accuracy, reliability, and consistency, as they are vulnerable to unreliable information.